Recent Advances in the Therapeutic Efficacy of Artesunate - Ngonidzashe Ruwizhi; Rejoice Bethusile Maseko; Blessing Atim Aderibigbe (MDPI AG, 2022)
Artesunate, a semisynthetic artemisinin derivative, is well-known and used as the first-line drug for treating malaria. Apart from treating malaria, artesunate has also been found to have biological activity against a variety of cancers and viruses. It also exhibits antidiabetic, anti-inflammatory, anti-atherosclerosis, immunosuppressive activities, etc. During its administration, artesunate can be loaded in liposomes, alone or in combination with other therapeutic agents. Administration routes include intragastrical, intravenous, oral, and parenteral. The biological activity of artesunate is based on its ability to regulate some biological pathways. This manuscript reports a critical review of the recent advances in the therapeutic efficacy of artesunate.